THE EFFECT of PINEALOCTOMY on the DEVELOPING SUPERIOR Cervical GANGLION of the RAT - Ali, Hadi Jawad; Al-khafaji, Fadhil A.; Hamash., Mahmood H. (AL-Kindy College Medical Journal, 2011)
Back ground: In the present study Pinealoctomywas used to study the sympathetic innervations ofthe pineal gland by the superior cervical ganglion(SCG) of the albino rat.Objective: Following Pinealoctomy, it isexpected to observe the Chromatolysis reaction insome neurons of the SCG if they were to innervatethe pineal gland (i.e. retrograde Chromatolysischanges).Methods: Fifty albino rats were used in this study,Pinealoctomy was done, then after a different timeinterval ganglionectomy was done, in order tostudy the Chromatolysis in their cell body.Result: The present study has demonstrated thatthe most obvious Chromatolysis reaction in theneurons which innervate the pineal gland appearedone day following Pinealoctomy in the young andadult rats. In the SCG of animal, one weekfollowing Pinealoctomy,the number of the Chromatolysis neurons wasmuch less than these seen in the previouslymentioned oneday animals. In (2 – 6) weeks followingPinealoctomy, the number of the Chromatolysisneurons kept a constant decline.Conclusion: The work presented in this studyshowed that the method of tracing the innervationsof the pineal gland by removing the target tissue(the pineal gland in this study) appeared to bejustified and conclusive.It has also shown that younger animals, subjectedto Pinealoctomy, would react more vigorously withrespect to Chromatolysis than adult animals. Thepresent study has also demonstrate that thedistribution of these Chromatolysis neurons and forall age groups all over the ganglion beinginspected. However they were more abundant inthe rostral 2/3 of these ganglions.